SCHOOL WELCOMING AND INCLUSION OF CHILDREN IN REFUGEE SITUATIONS IN THE EARLY YEARS OF ELEMENTARY EDUCATION - Teixeira, Marcia (2024)
This article refers to research, which aimed to analyze how schools can contribute, through reception, to the inclusion of children in refugee situations, entering the initial years of elementary school. The investigation, of a theoretical nature, was developed in order to understand the phenomenon of refuge and the meanings that reception can have for the inclusion of these children in school. The data was collected, categorized and analyzed based on the works of Winnicott, a pediatrician and child psychoanalyst who investigated the emotional development of children in times of war, highlighting elements that contribute to the understanding of the reception processes at school. Productions that stood out in a bibliographic survey carried out on the Capes Periodicals Portal were also analyzed to understand the phenomenon of refuge. The results showed that refuge is a traumatic process with impacts that expose children to situations of physical, psychological, cultural and social vulnerability, which is why it is essential that schools develop reception strategies that consider their characteristics and emotional needs, with guidance and support for specific pedagogical practices for children who experienced refuge. .